PROCESS FOR GAS SEPARATION - CARATI, ANGELA; TAGLIABUE, MARCO; BROCCIA, PATRIZIA; RIZZO, CATERINA; CICCARELLI, LIBERATO, GIAMPAOLO (2010)
The present invention relates to a process for the separation of gases which comprises putting a mixture of gases in contact with a porous material, containing a silica matrix in which one or more metal oxides are possibly uniformly dispersed, which are selected from transition metals or from metals of groups IIIA, IVA and VA, having a surface area larger than 500 m2/g, a pore volume between 0.3 and 1.3 ml/g, a pore diameter smaller than 40 Angstrom and a XRD powder spectrum which does not have a crystalline structure, does not show any peak, and has a single broad diffraction line, or, in any case, a wide¬ spread scattering at angular values not higher than 2? = 5° with CuKa radiation, without any other scattering phenomena coherent for higher angular values. By means of the process of the present invention, the selective adsorption is obtained of at least one of the gases forming the gaseous mixture. These adsorbing materials are regenerable and are particularly suitable for bulk removal operations of acid gases from natural gas. La présente invention concerne un procédé de séparation de gaz qui comprend la mise en contact d'un mélange de gaz avec un matériau poreux contenant une matrice de silice dans laquelle sont éventuellement uniformément dispersés un ou plusieurs oxydes métalliques qui sont sélectionnés parmi les métaux de transition ou parmi les métaux des groupes IIIA, IVA et VA, présentant une surface spécifique supérieure à 500 m²/g, un volume de pores compris entre 0,3 et 1,3 ml/g, un diamètre de pore inférieur à 40 Angströms et un spectre de diffraction des rayons X sur poudre qui ne possède pas de structure cristalline, ne présente aucun pic et possède une seule ligne de diffraction large ou, en tout cas, possède une diffusion étendue à des valeurs angulaires non supérieures à 2? = 5 ° avec un rayonnement CuKa, sans autre phénomène de diffusion cohérent pour des valeurs angulaires supérieures. Au moyen du procédé de la présente invention, l'adsorption sélective d'au moins l'un des gaz formant le mélange gazeux est obtenue. Ces matériaux adsorbants peuvent être régénérés et sont particulièrement appropriés pour des opérations d'élimination massive des gaz acides du gaz naturel.